POTASSIUM-ARGON ANALYSIS OF DOMAL SALT BY STEPWISE DISSOLUTION (Journal of Sciences, Islamic Republic of Iran)
Potassium-argon analysis by stqwise dissolution provides a way to measure in detail the distribution of argon isotopes and potassium in rock salt. The method can be used for salt that contains only trace amounts of potassium, because the potassium and argon in detrital silicates within the salt are not released during the dissolution. Water may be used as the solvent when relatively large amounts (one gram or more) of salt are to be dissolved in each step of the analysis. Methanol may be used when relatively small amounts of salt are to be dissolved in each step, in order to obtain high spatial resolution of the distribution of potassium and argon in the salt. Although preliminary analyses show that potassium-argon relationships in the deformed salt of salt domes can be very complex, analysis of these relationships by stepwise dissolution of properly chosen samples should provide useful isotope correlations in cases where the amounts of atmospheric argon and radiogenic argon in the salt are comparable